Safety factor assessment of a tunnel face reinforced by horizontal dowels. (1st July 2017) - Pan, Qiujing; Dias, Daniel
Highlights: A continuous deformation zone to model the soil-dowels interaction. Discretization technique to generate a non-circular tunnel face failure mechanism. Validate of the implemented method with those of 3D numerical analysis. Abstract: The use of dowels as a reinforcement technique has been successfully applied to improve the tunnel face stability during excavation, for the sake of safety and for the construction speed. The conventional tunneling, e.g. the New Austrian Tunneling Method, promotes the use of such techniques in design for a maximum optimization of the tunnel support. In this work, the kinematic approach in combination with the strength reduction technique is employed to evaluate the safety factor of a reinforced tunnel face. The discretization technique is extended to generate the failure mechanism for a realistic tunnel face shape (non-circular shape). An interaction zone with finite thickness is used to model the interaction between the soils and the dowels. The width of the interaction zone introduces a new parameter in the optimization process. In order to validate the implemented method, the results are compared with those of numerical analysis, which shows that the developed approach is an efficient design tool for the safety factor assessment of a reinforced tunnel face. Several charts are provided for parametric analysis to discuss the influence of the bolt length, the bolt density and the soil shear strength.